The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1038/modpathol.3800766
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for SYT protein discriminates synovial sarcoma from other soft tissue tumors: analysis of 146 cases

Abstract: Synovial sarcoma in its classic biphasic form can be distinguished readily from other soft tissue lesions; however, monophasic and poorly differentiated forms are diagnostically more problematic. For this reason, we assessed the efficacy of immunostaining for SYT and SSX1 proteins, the gene products resulting from unique synovial sarcoma translocation, to distinguish synovial sarcoma from other soft tissue lesions. A total number of 146 cases were analyzed, including 47 synovial sarcoma cases (all of which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…21 Recently, an antibody to the SS18 gene product has been shown to be sensitive for identification of synovial sarcomas, but it is not specific and has not found general application. 22 MPNSTs have focal nuclear positivity for S100 protein in up to 67% of cases, which correlates with ultrastructural evidence of Schwann cell differentiation. 23 Table 1.…”
Section: Malignant Spindle Cell Neoplasmsmentioning
confidence: 73%
See 1 more Smart Citation
“…21 Recently, an antibody to the SS18 gene product has been shown to be sensitive for identification of synovial sarcomas, but it is not specific and has not found general application. 22 MPNSTs have focal nuclear positivity for S100 protein in up to 67% of cases, which correlates with ultrastructural evidence of Schwann cell differentiation. 23 Table 1.…”
Section: Malignant Spindle Cell Neoplasmsmentioning
confidence: 73%
“…Synovial sarcomas are characterized by a specific chromosomal translocation t(X;18)(p11.2;q11.2), which results in fusion of the SS18 ( SYT ) gene from chromosome 18 with one of several variants of the SSX gene on the X chromosome 21 . Recently, an antibody to the SS18 gene product has been shown to be sensitive for identification of synovial sarcomas, but it is not specific and has not found general application 22 …”
Section: Spindle Cell Tumoursmentioning
confidence: 99%
“…TLE1 is a transcriptional corepressor overexpressed in synovial sarcoma; diffuse nuclear staining with anti-TLE1 antibody is seen in SS, whereas MPNST is typically negative [ 139 ]. Determination of SYT status by immunohistochemistry may be similarly helpful [ 140 ], being consistently positive in SS, paralleling the expected SYT-associated translocations demonstrable by FISH [ 141 ] or other molecular modalities; SYT alterations, in contradistinction, are not expected in MPNSTs. Leiomyosarcoma and solitary fi brous tumor are two other mimics; happily, immunopositivity for smooth muscle actin (SMA) and diffuse CD34 positivity, respectively, reliably separate these spindle cell neoplasms from MPNST.…”
Section: Differential Diagnosismentioning
confidence: 93%
“…TLE1 protein is also involved in the Wnt/β-catenin signaling pathway associated with SS, where it replaces TLE1-TCT/LEF complexes that repress transcription [18][19][20]. Genetic studies have identified TLE1 as a robust biomarker for differentiating SS from its histologic identicals [21][22][23].…”
Section: Introductionmentioning
confidence: 99%